Model Talking Stick dan Kemampuan Berbicara - Fathurrohman, Fathurrohman (LP3M STITNU AL HIKMAH MOJOKERTO, 2019)
This article aims to find out the thoroughness of mathematics learning outcomes of third grade students SD Islam Tarbiyatul Athfal Surabaya after the application of Talking Stick model. This type of research is a quasi experiment with Pre-test and Post-test group design. The population of all third grade students SD Islam Tarbiyatul Athfal Surabaya Lesson Year 2019/2020 amounted to 38 students and as a sample of class III3 taken at random. Data collection is done by test technique. The collected data were analyzed by using t test. Based on the results of the analysis data with the level of trust Î± = 0.05 obtained tcount (1.85)> ttable (1.68), so it can be concluded that the result of thematic learning of third grade students SD Islam Tarbiyatul Athfal Surabaya after applied Talking Stick method significantly completed . Average student learning outcomes of 79.97 and the percentage of complete students reached 79%.